PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB GOOGLE SITE PADA MATA PELAJARAN PROJEK KREATIF DAN KEWIRAUSAHAAN - Aprilia, Fara; Dwijayanti, Renny (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
Education is a crucial factor in creating quality human resources and determining the progress of a country. In today's era, teachers are required to design learning by creating learning media that aligns with technology. This research and development aims to determine the stages of development, feasibility, and student responses to web-based learning media using Google Sites in the subject of Creative Projects and Entrepreneurship. The type of research used is research and development (R&D) following the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The subjects of the trial were students from class XI Digital Business 1 and 2 at SMK PGRI 13 Surabaya. The research instruments included review sheets, expert validation sheets, and student response sheets. Data analysis techniques were conducted by analyzing the results of expert reviews, expert validation, and student responses. The results of the research using the ADDIE development model showed that the feasibility of the web-based learning media according to the material expert was 91.11%, the language expert was 84%, and the media expert was 86%. Student responses to the web-based learning media using Google Sites were rated as very good, with a score of 90.32%, indicating that the learning media is suitable for use and received positive feedback from students.